DIALEKTIKA TEATER KONDOBULENG MAKASSA DALAM KONTEKS PENDIDIKAN ANTAR GENERASI - Devalia Wahid Salsabillah; Malarsih Malarsih; Eko Sugiarto (Universitas Negeri Makassar, 2025)
This study aims to understand the role of Kondobuleng Theater in Makassar as a medium for intergenerational education through the dialectic of past and present values. This study is motivated by the ever-evolving changes in presentation forms and meanings, necessitating an in-depth analysis of the function of traditional theater in strengthening cultural identity amidst the currents of modernization. The study uses a qualitative approach with a phenomenological design and an interdisciplinary study of cultural sociology, obtained through participatory observation, in-depth interviews, and documentation. The results show that Kondobuleng Theater functions not only as entertainment, but also as a space for dialogue between the old and new generations. The older generation emphasizes historical, spiritual, and sacred values, while the younger generation articulates them critically, contextually, and participatoryly. This dialectic gives rise to new forms of performance that remain rooted in tradition, while also relevant to the needs of modern society. The novelty of this research lies in mapping the role of Kondobuleng Theater as a means of cross-age education with a dialectical framework that demonstrates cultural continuity and negotiation, thus having implications for traditional art preservation strategies based on presentation innovation, strengthening cultural literacy, and empowering local arts communities.